Integrating Sustainability Practices in Hospitality Management and Operations: An Analysis of Leadership Approaches, Green Certification, and Hotel Classification - Wisnawa, I Made Bayu (Akademi Komunitas MAPINDO, 2024)
The hospitality industry, as one of the largest consumers of energy, faces increasing pressure to adopt sustainability practices in the face of climate change and environmental damage. This study examines the role of participatory leadership, green certification, and hotel classification systems in integrating sustainability practices in the hospitality sector. By using qualitative descriptive methods through literature studies, this study identifies that the adoption of green technology and efficient operation can lower operational costs and improve public image. Furthermore, the study shows that green certification has a significant effect on guest booking decisions, signaling the importance of sustainability practices as a value-added in hotel marketing. Hotel classification systems that integrate sustainability standards offer a framework for assessing and categorizing hotels, encouraging hotels to continuously improve their sustainability practices. The results of this study are expected to provide insights for hotel managers to develop greener and socially responsible operational strategies, as well as support policies that promote environmental sustainability in hotel management.